Mrs. Pollifax, innocent tourist - Gilman, Dorothy, 1923-2012 (Fawcett Gold Medal, 1997)
Working with her retired CIA friend John Farrell, Mrs. Pollifax must smuggle a manuscript out of Jordan, a document that encodes the shocking truth of Saddam Hussein's reign. Hardly are the two airborne when the coils of Middle Eastern intrigue begin to unwind. Mrs. Pollifax's seatmate is not the affable Arab businessman he pretends to be. It is not imagination that persuades Mrs. P. that wherever they go, she and Farrell are followed. To elude their pursuers in such a politically volatile country isn't easy. In fact, it can be downright deadly.